Effect of biochar amendment on nitrate retention in a silty clay loam soil - Libutti, Angela; Mucci, Massimo; Francavilla, Matteo; Monteleone, Massimo (Italian Journal of Agronomy, 2016)
Biochar incorporation into agricultural soils has been proposed as a strategy to decrease nutrient leaching. The present study was designed to assess the effect of biochar on nitrate retention in a silty clay loam soil. Biochar obtained from the pyrogasification of fir wood chips was applied to soil and tested in a range of laboratory sorption experiments. Four soil treatments were considered: soil only (control), soil with 2, 4 and 8% of biochar by mass. The Freundlich sorption isotherm model was used to fit the adsorbed amount of nitrate in the soil-biochar mixtures. The model performed very well in interpreting the experimental data according to a general linear regression (analysis of co-variance) statistical approach. Nitrate retention in the soilbiochar mixtures was always higher than control, regardless the NO3 – concentration in the range of 0-400 mg L–1. Different sorption capacities and intensities were detected depending on the biochar application rate. The highest adsorption capacity was observed in the soils added with 2 and 4% of biochar, respectively. From the results obtained is possible to infer that nitrate retention is higher at lower biochar addition rate to soil (2 and 4%) and at lower nitrate concentration in the soil water solution. These preliminary laboratory results suggest that biochar addition to a typical Mediterranean agricultural soil could be an effective management option to mitigate nitrate leaching.